The genetic diversity of wild rescuegrass is associated with precipitation levels - Cuyeu, Alba Romina; Pagano, Elba Maria; Rosso, Beatriz Susana; Soto, Gabriela Cinthia; Ayub, Nicolás Daniel (Springer, 2017)
The genus Bromus belongs to the family Poaceae, contains over 160 annual and perennial species of grasses, varying in ploidy level from diploid (2n = 14) to dodecaploid (2n = 70) (Fortune et al. 2008). One of the most relevant species of Bromus in agriculture is Bromus catharticus Vahl, also known as rescuegrass (Belesky et al. 2007). B. catharticus is a winter annual grass, widely grown throughout the humid temperate regions. This species plays a critical role in forage and livestock systems, forming the plant basis for beef and milk production worldwide. B. catharticus is generally considered as an autogamous species, with an outcrossing rate of only 1.8% (Newell 1973). Thus, the genetic diversity of rescuegrass could be low due to this reproductive behaviour. However, the real genetic variability of this species remains unclear.